Classification of Metastatic versus Non-Metastatic Axillary Nodes in Breast Cancer Patients: Value of Cortex-Hilum Area Ratio with Ultrasound - Song, Sung Eun; Seo, Bo Kyoung; Lee, Seung Hwa; Yie, Ann; Lee, Ki Yeol; Cho, Kyu Ran; Woo, Ok Hee; Cha, Sang Hoon; Kim, Baek Hyun (Journal of breast cancer, 2012)
To investigate the significance of the cortex-hilum (CH) area ratio and longitudinal-transverse (LT) axis ratio and the blood flow pattern for diagnosis of metastatic axillary lymph nodes by ultrasound in breast cancer patients. From October 2005 to July 2006, we prospectively evaluated axillary nodes with ultrasound in 205 consecutive patients who had category 4B, 4C or 5 breast lesions according to the Breast Imaging Reporting and Data System-Ultrasound (BI-RADS-Ultrasound®). Among the 205, there were 24 patients who had pathologic verification of breast cancer and axillary lymph node status. For a total of 80 axillary nodes we measured the areas of the cortex and hilum of lymph nodes and calculated the area ratio. We also measured the length of the longitudinal and transverse axis of the lymph nodes and calculated the length ratio. We evaluated the blood flow pattern on power Doppler imaging and classified each lymph node into a central or peripheral pattern. Diagnostic performance was analyzed according to positive criteria for lymph node metastasis (CH area ratio >2, LT axis ratio <2, peripheral type on power Doppler imaging). The sensitivity of the CH area ratio was superior to that of the LT axis ratio (94.1% vs. 82.3%, p=0.031) and to that of the blood flow pattern (94.1% vs. 29.4%, p=0.009). For specificity, all three evaluating parameters had high values (89.1-95.6%) and no significant differences were found (p=0.121). The CH area ratio had a better positive predictive value than the LT axis ratio (94.1% vs. 80.0%, p=0.030) and power Doppler imaging (94.1% vs. 66.6%, p=0.028). For the negative predictive value, the CH area ratio was superior to the LT axis ratio (95.6% vs. 86.6%, p=0.035) and the blood flow pattern (95.6% vs. 63.0%, p=0.027). We recommend the CH area ratio of an axillary lymph node on ultrasound as a quantitative indicator for the classification of lymph nodes. The CH area ratio can improve diagnostic performance when compared with the LT axis ratio or blood flow pattern.